Comparison of Metabolome and Functional Properties of Three Korean Cucumber Cultivars - Jo, Hyo Eun; Son, Su Young; Lee, Choong Hwan (Frontiers in Plant Science, 2022)
Cucumber (Cucumis sativus L.) is consumed worldwide and various cultivars have been developed to enhance fruit quality. However, few studies have comprehensively evaluated the quality of various cultivars. We carried out a metabolomics approach to study the three different cucumber cultivars (Chuichung, White Dadagi, and Mini) and their parts (peel and flesh) coupled with antioxidant activities. The amino acids, sugars, flavonoids, carotenoids, and chlorophylls were upregulated in Mini flesh; however, in the case of peel, they were highly expressed in Chuichung. The highest antioxidant activity was observed in the peel of Chuichung and flesh of Mini. Through correlation analysis between metabolites and antioxidant activity, apigenin and quercetin derivatives, chlorophyll a, chlorophyll b, lutein, α-carotene, and β-carotene were found to be significantly positively correlated with antioxidant activity. To understand the metabolism of these compounds, we performed a comprehensive pathway analysis using a metabolomics approach and analysis of associated gene expression. In secondary metabolism, the expression levels of carotenoid-related genes (15-cis-phytoene synthase and ζ-carotene desaturase) and chlorophyll-related genes (protochlorophyllide reductase and glutamyl-tRNA reductase) were consistent with the metabolome analysis data. Collectively, carotenoid and chlorophyll metabolism were upregulated in Chuichung peel and Mini flesh, which had the highest antioxidant activity in each part. These bioactive compounds can be used as biomarkers of commercial cucumber fruit quality. Accordingly, this study offers integrative insights into the quality of different cucumber cultivars and explores valuable metabolites and genes that are helpful in improving quality with functional properties.